Reduction of SSR oscillations in power system network with STATCOM and UPFC - Sreeranganayakulu, J; V. Marutheswar, G; Sujatha, P (International Journal of Engineering and Technology, 2018)
SSR is a complex issue in electric power transmission network because of which the mechanical arrangement of a multi mass model encounters shaft harms. To keep away from this issue the mechanical oscillations which for the most part happen amid a balanced short circuit fault on the transmission network ought to be moderated by a few means. This paper delineates about the IEEE second benchmark framework which is demonstrated and simulated in MATLAB Simulink. The outcomes are compared when Static Synchronous Compensator (STATCOM) is incorporated and furthermore with those when Unified Power Flow Controller (UPFC) included for their viability in moderating the Subsynchronous Resonance motions.Â